Measuring high-efficiency perfect composite vortex beams with reflective metasurfaces in microwave band - Hong Jing; Ni Mengyi; Zhang Zhengping; Hu Zheng-Da; Wang Jicheng; Shen Xiaopeng; Wang Xiong; Li Mengmeng; Khakhomov Sergei (Nanophotonics)
Optical vortex beams carrying orbit angular momentum have attracted significant attention recently. Perfect vortex beams, characterized by their topological charge-independent intensity profile, have important applications in enhancing communication capacity and optimizing particle manipulation. In this paper, metal-insulator-metal copper-coin type reflective metasurfaces are proposed to generate perfect composite vortex beams in X-band. We introduce the qualified equivalent circuit model based on the theory of transmission line to design the meta-atom of the structure. The experiments are performed to measure the far-field and near-field perfect composite vortex beams and evaluate their orbital angular momentum purity at different frequencies. The experimental results agree well with the theoretical predictions. This work provides new ideas and methods for generating high-quality metasurface-based perfect composite vortex beams in the microwave region, paving an ideal path for microwave communication systems, optical manipulation and radar detection.